GAMBARAN ANGKA LEMPENG TOTAL DAN IDENTIFIKASI BAKTERI Escherichia coli PADA LOLOH BUNGA TELENG DI DESA PENGLIPURAN KECAMATAN BANGLI - nyoman mastra (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2021)
AbstractBackground : Teleng flower herb is a processed beverage made from teleng flower which is popular as a traditional drink from Penglipuran Village. As one of the beverage products, teleng flower herbs have to obtain consent from the BPOM before distributed and consumed. Purpose : this study was conducted to analyze the quality of microbiology of teleng flower herb. The analyzed parameters were total plate count (ALT) and E. coli bacteria identification. Method : this study used descriptive research with laboratory examinations which was conducted at the Bacteriology Laboratory. The 7 samples were obtained from producers with three times repetition so that it became 21 samples with sampling techniques were saturated sampling. Result : The ALT examination results show that 5 samples (71.4%) are not qualify and 2 samples (28.6%) are qualify based on BPOM Regulation Number 16 In 2016. The obtained results of E. coli identification show that there were 4 (57.1%) contain of E. coli pathogens and 3 samples (42.9%) are not contains of E. coli pathogens. It can be concluded that most of the hygiene of teleng flower herb at Penglipuran Village does not meet the requirements. Conclusion : Based on these results, we suggest to the producers of teleng flower herb to maintain the quality of teleng flower herb that they sell. Key words: teleng flower herb, microbiological quality, total plate count, E. coli